2022
DOI: 10.3389/fonc.2021.799993
|View full text |Cite
|
Sign up to set email alerts
|

Restoring p53 Function in Head and Neck Squamous Cell Carcinoma to Improve Treatments

Abstract: TP53 mutation is one of the most frequent genetic alterations in head and neck squamous cell carcinoma (HNSCC) and results in an accumulation of p53 protein in tumor cells. This makes p53 an attractive target to improve HNSCC therapy by restoring the tumor suppressor activity of this protein. Therapeutic strategies targeting p53 in HNSCC can be divided into three categories related to three subtypes encompassing WT p53, mutated p53 and HPV-positive HNSCC. First, compounds targeting degradation or direct inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 105 publications
0
29
0
Order By: Relevance
“…The transcriptional activity of p53 was significantly increased by 4HR administration in both YD-15 and YD-9 cells. Several chemicals have been identified that can change the conformation of mutant p53 ( 9 ). However, most of these increase the production of ROS ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The transcriptional activity of p53 was significantly increased by 4HR administration in both YD-15 and YD-9 cells. Several chemicals have been identified that can change the conformation of mutant p53 ( 9 ). However, most of these increase the production of ROS ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The TP53 mutation is a frequent finding in oral cancer ( 7 , 8 ). Several strategies against mutant TP53 have been developed ( 8 , 9 ). The most frequent site of TP53 mutation is the DNA-binding site ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, re-purposing is not the only option, and there are a number of small molecule drugs being developed to restore wild-type activity in mutant p53 [ 171 ]. A recent review of such strategies in head and neck squamous cell carcinoma, a malignancy with high rates of somatic TP53 mutations, included the agents PRIMA-1, APR-246, RITA, COTI-2 and CP-31398 [ 172 ]. Another interesting avenue of exploration is zinc metallochaperones (ZMCs)—small molecule agents that reactivate zinc-deficient p53 mutants [ 173 ].…”
Section: Drugging the Undruggablementioning
confidence: 99%